2020
DOI: 10.21010/ajid.v14i1.1
|View full text |Cite
|
Sign up to set email alerts
|

CALLUS INDUCTION OF Sonchus arvensis L. AND ITS ANTIPLASMODIAL ACTIVITY

Abstract: Background: Malaria is a global health problem that requires urgent need for new drugs. Tempuyung (Sonchus arvensis L.) possesses many potential medicinal compounds. As the plant is originally found wild, it is important to reproduce its secondary metabolites by tissue culture. The objectives of this study were to look for effective methods to induce callus from leaf explants of Sonchus arvensis L. and to test its in vitro antiplasmodial activity. Materials and Methods: The leaves and petioles of the plant wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…The antiplasmodial test referred to the method of Rieckmann et al [22], which was later modified by Wahyuni et al [11]. The callus extract was tested against P. falciparum strain 3D7 at ring stage.…”
Section: In Vitro Antiplasmodial Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The antiplasmodial test referred to the method of Rieckmann et al [22], which was later modified by Wahyuni et al [11]. The callus extract was tested against P. falciparum strain 3D7 at ring stage.…”
Section: In Vitro Antiplasmodial Activity Assaymentioning
confidence: 99%
“…Many studies show that S. arvensis L. possesses antioxidant activity, uric acid-lowering activity, anti-inflammatory activity [8], immunomodulatory activity [9], and antibacterial activity [10]. In addition, a previous report showed that S. arvensis L. callus has antimalarial activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Conservation and large scale production of these bioactive secondary metabolites are additional benefits of in vitro techniques. It's on the strength of this technique that Wahyuni et al [14] reported a protocol for callus induction explants (leaf) from S. arvensis and determined its antimalarial activity by in vitro assay. According to their report, the combination of 1mg/L 2,4-D and 0.5 mg/L BAP yield maximum callus within a short time and the in vitro assay has a significant antimalarial activity [14].…”
Section: Sonchus Arvensis Lmentioning
confidence: 99%
“…It's on the strength of this technique that Wahyuni et al [14] reported a protocol for callus induction explants (leaf) from S. arvensis and determined its antimalarial activity by in vitro assay. According to their report, the combination of 1mg/L 2,4-D and 0.5 mg/L BAP yield maximum callus within a short time and the in vitro assay has a significant antimalarial activity [14]. The report suggests that S. arvensis callus extract is an excellent potential candidate for malaria treatment.…”
Section: Sonchus Arvensis Lmentioning
confidence: 99%
“…In addition to being an early successional inhabitant on recently disturbed sites, S. arvensis is known for containing several active pharmaceutical compounds (Lemna and Messersmith 1990 ; Wahyuni et al. 2020 ). In the case of the phylogenetic position of S. arvensis , it is closely related to diploid (2 n = 2 x = 18) perennial species of Sonchus , including S. maritimus and S. crassifolius in sect.…”
mentioning
confidence: 99%